Adverse Maternal Outcomes and Associated Factors Among Mothers of Advanced Age delivering at a Tertiary Hospital, Southwestern Uganda: A Cross-Sectional Study. - Masembe, Sezalio; Migisha, Richard; Turyasingura, Godwin; Aheisibwe, Hillary; Nzabandora, Emmanuel; Lule, John C. (Kabale University, 2024)
Background Mothers of advanced age, defined as pregnant women aged≥35 years at the time of giving birth, are traditionally known to be associated with increased risks of adverse maternal outcomes. We determined the prevalence of adverse maternal outcomes and associated factors among mothers of advanced age who delivered at Kabale Regional Referral Hospital (KRRH), in Southwestern Uganda. Methods. We conducted a cross-sectional study at the Maternity Ward of KRRH from April to September 2023. We consecutively enrolled pregnant women aged≥35 years during their immediate post-delivery period and before discharge. We obtained data on their socio-demographic, obstetric, and medical characteristics and their maternal outcomes using interviewer-administered questionnaires. We define adverse maternal outcome as any complication sustained by the mother that was related to pregnancy, delivery, and immediate post-partum events (obstructed labor, antepartum hemorrhage, mode of delivery [cesarean or vacuum extraction], postpartum hemorrhage, hypertensive disorders of pregnancy, preterm or postdate pregnancy, anemia, premature rupture of membranes, multiple pregnancy, and maternal death). A participant was considered to have an adverse outcome if they experienced any one of these complications. We identified factors associated with adverse outcomes using modified Poisson regression. Results Out of 417 participants, most were aged 35–37 years (n=206; 49.4%), and had parity≥5 (65.5%). The prevalence of adverse maternal outcomes was 37.6% (n=157, 95%CI: 33.1–42.4%). Common adverse maternal outcomes included caesarian delivery (23%) and obstructed labor (14.4%). Other complications included anemia in pregnancy (4.5%), chorioamnionitis (4.1%), preterm prelabour rupture of membranes (3.9%), and chronic hypertension and preeclampsia (both 2.4%). Factors associated with adverse maternal outcomes were precipitate labor (adjusted prevalence ratio [aPR]=1.95, 95%CI: 1.44–2.65), prolonged labor, lasting>12 h (aPR=2.86, 95%CI: 1.48–3.16), and chronic hypertension (aPR=2.01, 95%CI: 1.34–3.9). Conclusion Approximately two-fifth of the advanced-aged mothers surveyed had adverse outcomes. Mothers with prolonged labor, precipitate labor, and chronic hypertension were more likely to experience adverse outcomes. We recommend the implementation of targeted interventions, emphasizing proper management of labor as well as close monitoring of hypertensive mothers, and those with precipitate or prolonged labor, to mitigate risks of adverse outcomes within this study population.